Ketahanan Berbagai Kultivar Padi Lokal terhadap Penyakit Hawar Daun Bakteri - Andi Khaeruni; Erwin Najamuddin; Teguh Wijayanto; Syair Syair (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Bacterial leaf blight disease caused by Xanthomonas oryzae pv. oryzae is an important rice disease in Indonesia, including in South East Sulawesi. The use of resistant varieties is one of the effective and environmentally friendly control strategies to suppress the disease. This study aimed to determine the level of resistance of some local rice varieties of South and Southeast Sulawesi against Xanthomonas oryzae pv. oryzae pathotypes IV, VIII and X. The study was conducted in a screen house involving 3 bacterial pathotypes and 11 local rice cultivars. Shearing method was used for inoculation of bacteria to leaf on vegetative and generative phases. Disease incidences were measured 3 weeks after inoculation, and the data was further used to determine the level of resistance of the tested rice cultivars. The results showed that incubation period of the disease was longer on Kelaca cultivar compared to other cultivars. On vegetative phase, this cultivar showed moderate resistant to pathotypes IV and X, and highly resistant to patotype VIII, whereas on the generative phase it showed moderate resistant to pathotypes IV and VII, and highly resistant to pathotype X. Therefore, Kelaca cultivar can be recommended for endemic areas of leaf blight in South and Southeast Sulawesi